ANALISIS FINANCIAL DISTRESS MENGGUNAKAN MODEL ALTMAN Z -SCORE DAN SPRINGATE PT BINAKARYA JAYA ABADI, Tbk PERIODE 2016-2020 - Zakaria Hamzah, Zeze; Fitriyani; Muhlis; Satria Rukmana, Heru; Muchammad Hamdani (Sekolah Tinggi Ilmu Ekonomi Dewantara, 2023)
This research is about financial distress analysis using the Altman Z Score and Springate models to predict financial distress in property companies, especially PT Binakarya Jaya Abadi, Tbk for the 2016-2020 period. The results of this analysis are two results obtained from the Altman Z modelScore and Springate. The results of the prediction of financial distress are for the Altman Z-Score model in 2016 to obtain a ratio of 2.7470 indicating a prediction of not going bankrupt, in 2017 obtaining a ratio of 3.8066 indicating a prediction of not going bankrupt, in 2018 obtaining a ratio of 3.5711 indicating prediction of not going bankrupt, in 2019 obtaining a ratio of 3.2854 indicating a prediction of not going bankrupt and in 2020 obtaining a ratio of 0.6885 indicating a prediction of bankruptcy. Whereas for the Springate model in 2016 it obtained a ratio of 0.3999 indicating a prediction of bankruptcy, in 2017 it obtained a ratio of 0.5862 indicating a prediction of bankruptcy, in 2018 it obtained a ratio of 0.5526 indicating a prediction of bankruptcy, in 2019 it obtained a ratio of 0 .4408 indicates a prediction of bankruptcy and in 2020 obtains a ratio of 0.0292 indicating a prediction of bankruptcy.